Finishing properties of lacquer by using different methods of application on sepetir / Noor Shafiqah Supangat - Supangat, Noor Shafiqah (Faculty of Applied Sciences, 2015)
The wood finishing is the process of embellishing and/or protecting the surface of a wooden material. In this study, Sepetir was used to substitute the shortage of the commercial timber and as alternative supply for furniture industry. The objective of the study was to identify the properties of finishing using polyurethane lacquer and nitrocellulose lacquer on Sepetir wood species. Furthermore, to investigate the finishing performance of lacquer by using different types of application methods which were brush application and spray application. Two types of lacquer and three types of testing were used in this study. Generally, the result shows the highly significant between lacquer and methods of application. The overall results of the study were discussed.